Faktor Penyebab Cemas Pada Pekerja Wanita Usia Subur - Febriawati, Henni; Wati, Zulaikha Agustina; Angraini, Wulan; Yanuarti, Riska; Puteri, Febyona Jolest (MAHESA : Malahayati Health Student Journal, 2024)
ABSTRACT According to the East Java Province Communication and Information Service, in 2023 the number of female workers in East Java will increase by 0.47%. 56.11% of workers in East Java are women. This study aims to determine the factors of depression/anxiety in female workers of childbearing age (WUS) with an age range of 15-49 years. The research design used is mixed methods research by combining quantitative data (Self-Reporting Questionnaire (SRQ)-20 test) and qualitative data (in-depth interviews). The results of the Self-Reporting Questionnaire (SRQ)-20 test show that 3 out of 15 female workers of childbearing age experience depression/anxiety. The results of in-depth interviews (In-Depth Interview) show that there are factors that cause depression/anxiety in female workers of childbearing age, namely work factors and individual (family) factors. The conclusion of this research is that there is a relationship between depression/anxiety and reproductive health in female workers of childbearing age. Keywords: Anxiety, Women of Childbearing Age, Worker  ABSTRAK Menurut Dinas Kominfo Provinsi Jawa Timur tahun 2023, jumlah pekerja wanita di Jawa Timur meningkat 0,47%. 56,11% pekerja di Jawa Timur adalah wanita. Tujuan penelitian ini untuk mengetahui faktor depresi/cemas pada pekerja Wanita Usia Subur (WUS) dengan rentang usia 15-49 tahun. Desain penelitian yang digunakan adalah mixed methods research dengan menggabungkan data kuantitatif (tes Self-Reporting Questionnaire (SRQ)-20) dan data kualitatif (wawancara mendalam). Hasil tes Self-Reporting Questionnaire (SRQ)-20 diperoleh 3 dari 15 orang pekerja wanita usia subur mengalami depresi/cemas. Hasil wawancara mendalam (In-Depth Interview) menunjukkan adanya faktor penyebab depresi/cemas pada pekerja wanita usia subur yaitu dikarenakan faktor pekerjaan dan faktor individu (keluarga). Kesimpulan dari penelitian ini adalah adanya hubungan antara depresi/cemas dengan kesehatan reproduksi pada pekerja wanita usia subur. Kata Kunci: Cemas, Pekerja, Wanita Usia Subur